Community-Based Empowerment Of People Living With Hiv/Aids (Plwhas) Through Community-Based Organisations In Malaysia - Jaganathan, Paramaswari (2010)

(untitled)
HIV/AIDS is a global crisis and it affects all strata of the society. In the National Strategic Plan on HIV/AIDS (2006-2010), the government acknowledges the role of non-governmental organisations and community-based organisations; particularly to reduce the spread of the virus among hard-to-reach groups such as commercial sex workers, drug users and homosexuals. This study gives an insight into the approaches used by three HIV/AIDS community-based organisations in Penang to empower the PLWHAs. It aims to analyse the strategies used by the community-based organisations to handle the psychosocial issues faced by PLWHAs as well as factors that affect the empowerment of the PLWHAs. This is a qualitative study that employs interviews, participant observation and involvement in activities carried out by the community-based organisation.